Tecnología vestible una ventaja competitiva en el entrenamiento deportivo (2020)
This document contains an overview of wearable technology and the origin, related topics, and authors of the main publications on this topic related to this century. It is important to say that wearable or wearable technology is also known as “wearables” in the English language and refers to the incorporation of microprocessors, sensors and transducers in the elements that dress us daily, which acts as computers that always go with The user and that is capable of being used in a defined space to continuously interact with the user, wearable technology can be defined as electronic devices capable of being incorporated into the body of a person, in order to obtain information continuously. The objective of this document is to know the evolution and state of the art of this new technology, to apply it to new research findings and the creation of wearable devices. The disciplinary union between different areas of knowledge obtains with this document a clear starting point for the development of research topics, in the particular case of interest, focused on devices applied to sport, for the analysis of the strength, flexibility and speed of Lower limbs of the athlete, generating sports tests that relate numerical data, for the subsequent analysis, interpretation and generation of conclusive results. Electronic engineering performs all the transformation from analog to electrical data, which defines a design of wearables that are adaptable for physical activity. In the field of programming, systems engineering is important for the conversion of sensor data and the presentation of this data in a way that people can understand. This new technology allows the generation of a great variety of data, but at the same time it integrates multiple disciplines. With the knowledge of physical culture, the complex issues that surround the human body when developing a physical activity and the correct way of interpreting the results are tested, on wearable elements that can be designed from technology.